Early enteral nutrition and mortality in mechanically ventilated septic patients receiving vasopressors: A retrospective cohort study using the MIMIC-IV database - Bo Zou; Fengchan Xi; Tao Gao; Wenkui Yu (PLoS ONE, 2025)
Background The role of early enteral nutrition (EEN) in septic shock remains unclear. This study aimed to evaluate the association between EEN and clinical outcomes in septic patients requiring vasopressor therapy and invasive mechanical ventilation. Methods This retrospective cohort study used the MIMIC-IV database and included adult septic patients receiving vasopressors and mechanical ventilation at ICU admission. EEN was defined as enteral nutrition initiated within 48 hours. The primary outcome was 28-day mortality. Secondary outcomes included ICU and hospital length of stay, and duration of mechanical ventilation. Inverse probability of treatment weighting (IPTW) was used to adjust for baseline confounders. Vasopressor dose was stratified based on the maximum norepinephrine-equivalent dose in the first 48 hours: low (<0.1 micrograms/kg/min), medium (0.1–0.5), and high (>0.5). Multivariable regression models were used to assess associations. Results A total of 4,673 patients were included, of whom 997 (21.3%) received EEN. Before weighting, EEN was associated with higher 28-day mortality (21.9% vs. 15.3%). After IPTW adjustment, early feeding remained significantly associated with increased mortality (adjusted odds ratio 1.80; 95% confidence interval, 1.42 to 2.27). In stratified analyses, EEN was associated with increased mortality in the medium-dose (odds ratio 1.66; 95% confidence interval, 1.26 to 2.19, p < 0.001) and high-dose groups (1.90; 1.21 to 2.98, p < 0.001), but not in the low-dose group(1.92, 1.12 to 3.27, p = 0.016). Conclusions In critically ill septic patients receiving vasopressors and mechanical ventilation, EEN was associated with increased 28-day mortality, particularly among those receiving medium- or high-dose vasopressor therapy.